Retinal Ganglion Cells Functional Changes in a Mouse Model of Alzheimer S Disease Are Linked with Neurotransmitter Alterations - Chacon-Pacheco, M; Bello-Robles, F (IOS Press BV, 2021)
Alzheimer s disease (AD) is the most prevalent form of dementia worldwide. This neurodegenerative syndrome affects cognition, memory, behavior, and the visual system, particularly the retina. Objective: This work aims to determine whether the 5xFAD mouse, a transgenic model of AD, displays changes in the function of retinal ganglion cells (RGCs) and if those alterations are correlated with changes in the expression of glutamate and gamma-aminobutyric acid (GABA) neurotransmitters. Methods: In young (2-3-month-old) and adult (6-7-month-old) 5xFAD and WT mice, we have studied the physiological response, firing rate, and burst of RGCs to various types of visual stimuli using a multielectrode array system. Results: The firing rate and burst response in 5xFAD RGCs showed hyperactivity at the early stage of AD in young mice, whereas hypoactivity was seen at the later stage of AD in adults. The physiological alterations observed in 5xFAD correlate well with an increase in the expression of glutamate in the ganglion cell layer in young and adults. GABA staining increased in the inner nuclear and plexiform layer, which was more pronounced in the adult than the young 5xFAD retina, altering the excitation/inhibition balance, which could explain the observed early hyperactivity and later hypoactivity in RGC physiology. Conclusion: These findings indicate functional changes may be caused by neurochemical alterations of the retina starting at an early stage of the AD disease. © 2021 - IOS Press. All rights reserved.